The limits of philosophy. Nikolai Fedorov and the project of the common task - Jędrysko, Cezar (Hybris, 2014)
This paper is a presentation of Nikolai Fedorov’s main and only idea: the abolition of death and the resurrection of the dead of all generations. Fedorov’s philosophy is a unique mix of theological and futuristic-utopian narratives. Firstly, I take a look at Fedorov’s religious assumptions: the relation between God and man and the meaning of Lazarus' resurrection for mankind. Secondly, I examine the social and technological conditions which have to be fulfilled in order to animate the dead bodies of our forefathers. Then, I try to characterize Fedorov’s thinking as a deontological moral philosophy based on the concept of imperative. I arrive at the conclusion that Fedorov’s project, on the one hand, exceeds and, on the other hand, extends the limits of what we call “philosophy”. Additionally, some recent contexts of Fedorov’s idea in modern Russia will be mentioned in the article: Strategic Social Initiative 2045 and political party Evolution 2045.